Prospects for import substitution of the equipment in forming machine utilization systems in the agriculture of Siberian Federal District - Nardin, Dmitry Sergeevich; Pomogaev, Vitaly Mikhailovich; Nardina, Svetlana Aleksandrovna (International Journal of Economics and Financial Issues, 2015)
The goal of the research is to determine perspectives for import substitution of the equipment in the agriculture of Siberian Federal District. The paper contains methods for analyzing import substitution perspective lines, including sequential performance of the following stages: fist, analysis of technical equipment of agriculture branches in the region that provides for assessment of availability of the main types of agricultural equipment. The second stage includes assessment of the renewal rate of the equipment fleet the most in demand in the region. On this stage one should calculate number of the equipment purchased within the research period, as well as ratio of new equipment in the general fleet that was identified on the first stage. The third stage provides for identification and analysis of import of the main equipment, and determination of equipment import ratio within the research period. The fourth stage includes determination of import importance for equipment renewal in the regional agribusiness and validation of priorities of import substitution in forming the machine utilization system in the agriculture. As the result of the research the offered methods were tested on the materials of Siberian Federal District of the Russian Federation. The authors determined and validated priorities for equipment import substitution for the regional agriculture, as well as economic effects of import substitution. Keywords: import substitution, agriculture, machine utilization systems, economic efficiency, agribusiness technical equipment. JEL Classifications: O33, Q16, Q17